Ответы и объяснения

2013-02-16T12:05:46+04:00

a) cos(a)*sin(a+b)=cos(a)*(sin(a)cos(b)+cos(a)sin(b))=sin(a)cos(b)cos(a)+cos^2(a)sin(b)

 

а)(sin(a+b)+(sina-b)) / (cos(a+b)+cos(a-b))=tg (a)

 

(sin(a)*cos(b)+cos(a)*sin(b))+(sin (a)*cos(b)-cos(a)*sin(b)) / (cos(a)*cos(b)-sin(a)*sin(b))+(cos(a)*cos(b)+sin(a)*sin(b))=tg (a)

 

(2*sin(a)*cos(b)) /(2*cos(a)*cos(b))=tg(a)

 

sin(a)/cos(a)=tg (a)

 

tg (a)=tg (a)

 

б) (cos(a-b)-cos(a+b))/ (sin(a+b)-(sina-b))=tg(a)

 

(cos(a)*cos(b)+sin(a)*sin(b))-(cos(a)*cos(b)-sin(a)*sin(b)) / (sin(a)*cos(b)+cos(a)*sin(b))-(sin (a)*cos(b)-cos(a)*sin(b))=tg (a)

 

(2*sin(a)*sin(b)) /(2*cos(a)*sin(b))=tg(a)

 

sin(a)/cos(a)=tg (a)

 

tg (a)=tg (a)